New Report on The Occurrence of Gregarine Parasites in Wild Species of Macrobrachium rosenbergii from Setiu Lagoon, Terengganu, Malaysia - Mohd Ihwan Zakariah; Hassan Haji Mohd Daud; Mhd. Ikhwanuddin Abdullah; Wahidah Wahab; Farizan Abdullah; Nor Asma Husna Mohammed Yusoff; Ahmad Shuhaimi Draman; Marina Hassan (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchThis is the first report of the occurrence of gregarine species in Peninsular Malaysia.The information of these findings will lead to the identification of species using genetic analysis.This information can help to solve the cultured problem of the Macrobrachium rosenbergii industry worldwide. AbstarctStudies on the parasite of prawn are likely to be important due to the commercial value of the prawn. Investigation study about gregarine parasites of M. rosenbergii in Malaysia is still lacking. Objective of this study is to determine the occurrence of gregarine parasites in shrimp, M. rosenbergii from Setiu Lagoon, Terengganu. The study was done specifically to observe the prevalence and the mean intensity of the parasites which include the morphological prevalence and parasitological study. Prevalence of the parasites in this study is 42.4% with 95% Cumulative Index (CI) 25.6% to 59.3% and value of Odd Ratio (OR) is 0.74 (CI = 0.29 to 1.88). Two structures of the gregarine which is gamont and syzygy found in this study are closely related to morphology characteristic of gregarine in the previous report.